Meghdoot App to support the digitalization of agroadvisories in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Meghdoot, a joint initiative of India Meteorological Department (IMD), Indian Institute of Tropical Meteorology (IITM) and Indian Council of Agricultural Research (ICAR) aims to deliver critical information to farmers through a simple and easy to use mobile application. The app seamlessly aggregates contextualised district and crop wise advisories issued by Agro Met Field Units every Tuesday and Friday with the forecast and historic weather information to farmers in local vernacular. Meghdoot has disseminated >350k advisories with >45k active users.